English Strategy for Visually Impaired Students - Khodijah, Khodijah; Jabu, Baso; Muliati, A. (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research explores the strategies used by visually impaired students in learning English and the facilities they need to support their learning. Conducted at SLB-A Yapti Makassar, the study employed a qualitative descriptive approach using interviews, observations, and documentation. The findings revealed that the visually impaired students utilized various strategies including audio-based learning, peer support, and memorization. The most crucial facilities for these students were assistive technology tools such as screen readers, braille books, and a supportive learning environment. Teachers also played a significant role in adapting materials and providing multisensory instruction. The study concludes that inclusive English language learning for visually impaired students requires collaborative strategies, accessible resources, and trained educators. These elements ensure that visually impaired learners can actively participate and succeed in language acquisition, thus promoting equitable education. Further research is encouraged to evaluate these strategies in broader educational contexts.